The Qur’anic story in teaching grammatical structures for non-native speakers of Arabic - Zamri Arifin,; Mohammad Saleh,; Lily Hanefarezan Asbulah, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The Qur’anic story has a distinct position in teaching Arabic to non-native speakers, and because many learners of the Arabic language who are non-native speakers face various problems in learning grammatical structures This research presents an attempt to overcome these problems, and seeks to reveal the importance of employing the Qur’anic story in teaching grammatical structures to non-native speakers of Arabic language, and to submit a suggestion to employ the Qur’anic story in teaching grammatical structures to non-native speakers of Arabic language, using the descriptive-analytical approach. The research shows the relationship of the Arabic language with the Holy Qur’an, the meaning of the Qur’anic story, its importance, purposes, types and characteristics, grammatical structures in terms of meaning and what should be taught to non-native speakers of Arabic language, the importance of teaching and learning grammar, the mistakes that learners of Arabic language who speak non-Arabic make, and the reason for teaching grammatical structures from during the Qur'anic story. The research suggests a method for teaching grammatical structures through the Qur'anic story. The results of the research concluded that the Qur’anic story is of great importance in teaching grammatical structures to non-native speakers of Arabic language due to its characteristics and features, and the variety of grammatical structures that it abounds in, which have the greatest impact on the learner.